Phospholipase A2 (PLA2) activity in mini pigs after acute high dose iv-paraoxon (POX) intoxication - Petroianu, Georg; Helfrich, Ursula; Globig, Susanne; Fisher, Joseph; Rüfer, Roderich (Chemico-biological interactions, 1999)
The purpose of the present study was to establish in the mini pig model the effects of paraoxon (POX) on PLA2 activity. Six anesthetized and mechanically ventilated mini pigs were infused over 50 min with 0.3, 1, 3, 9, 27 and 81 mg POX kg−1BW−1 dissolved in ethanol, respectively. The control animal received no POX but the ethanol amount corresponding to the highest POX dose. PLA2 activity measurements were carried out immediately after POX application. Data were analysed with the Mann-Whitney-Wilcoxon rank order test. Statistical significance was assumed for P≤0.05. Exposure to POX inhibited PLA2 activity to 50.5±8.9% of baseline activity. The changes seen were not dose-dependent. The dose dependency previously demonstrated in vitro was not reproducible in vivo. This is most probably due to the massive endogenous catecholamine release leading to PLA2 activation. An additional masking effect is due to the (co)administration of drugs needed for anesthesia and cardiovascular support, especially Mg2+. These substances also influence the PLA2 activity.
Elektronische Reproduktion der Druckausgabe
Im Titel ist die Zahl 2 jeweils tiefgestellt
Gesehen am 30.05.2022